New Trends in Immunohistochemical Methods to Estimate the Time since Death: A Review - Monica Salerno; Giuseppe Cocimano; Salvatore Roccuzzo; Ilenia Russo; Dario Piombino-Mascali; Nicholas Márquez-Grant; Christian Zammit; Massimiliano Esposito; Francesco Sessa (Diagnostics, 2022)
The identification of a reliable and accurate post-mortem interval (PMI) is a major challenge in the field of forensic sciences and criminal investigation. Several laboratory techniques have recently been developed that offer a better contribution to the estimation of PMI, in addition to the traditional physical or physico-chemical (body cooling, lividity, radiocarbon dating, rigor mortis), chemical (autolysis), microbiological (putrefaction), entomological, as well as botanical parameters. Molecular biology (degradation pattern of macromolecules such as proteins, DNA, RNA), biochemical analysis of biological fluids (such as blood, cerebrospinal fluid, and vitreous humor), and immunohistochemistry are some of the most recent technological innovations. A systematic review of the literature was performed with the aim of presenting an up-to-date overview on the correlation between the immunohistochemical (IHC) expression of specific antigenic markers at different PMIs. The systematic review was performed according to PRISMA guidelines. Scopus and PubMed were used as search engines from January 1, 1998 to March 1, 2022 to evaluate the effectiveness of immunohistochemistry in estimating PMI. The following keywords were used: (immunohistochemical) OR (immunohistochemistry) AND (time since death) OR (post-mortem interval) OR (PMI). A total of 6571 articles were collected. Ultimately, 16 studies were included in this review. The results of this systematic review highlighted that IHC techniques, in association with traditional methods, add, in Bayesian terms, additional information to define a more accurate time of death and PMI. However, current IHC results are numerically limited and more data and studies are desirable in the near future.